IMPACT OF TILLAGE AND RESIDUE MANAGEMENT ON ACID AND ALKALINE PHOSPHATASE ACTIVITIES OF RABI MAIZE - K. SAMMI REDDY; G. PRATIBHA, CH. RAVALI, G. JAYASREE, S. TRIVENI (The Journal of Research, PJTSAU, 2023)
A field experiment was conducted in college farm, College of Agriculture, Rajendranagar, PJTSAU, Hyderabad, to study different rice residue management options in conservation tillage and conventional tillage in rice-maize cropping system, during rabi 2020-21 and 2021-22. There were eight residue management options in each tillage system viz., T1- Total removal of residue and RDN (33:33:33), T2 - Residue incorporation/retention + RDN (33:33:33), T3- Residue incorporation/retention + RDN (33:33:33) + Microbial Consortium (2% Spray), T4 - Residue burning + RDN (33:33:33), T5- Residue incorporation/retention + RDN (43:23:33), T6 - Residue incorporation/retention + RDN (43:33:23), T7 - Residue incorporation/retention + 10 % extra RDN (43:23:33), T8 -Residue incorporation/retention + 10 % extra RDN (33:43:23). There were a total of 16 treatments, replicated thrice and laid in strip plot design. The results indicated that tillage and residue management options significantly affected acid and alkaline phosphatase activity as well as available P status in soil. Conservation tillage practice resulted in an increase of acid phosphatase activity by 9 % in rabi 2020-2021 and 16 % in rabi 2021-2022 over conventional tillage. The increase in the phosphatases activity with residue retention and incorporation led to increase in the available P status of soil during crop growth period till tasseling stage.